The Impact of Online Learning of English Language at University Level- Due the Circumstances of Corona Pandemic - Osman, Khalda Abdelrhim; Algmadi, Maryam Awadh; Algamdi, Hana Saeed (Advances in Social Sciences Research Journal, 2023)
This study aimed to determine the impact of online learning of English Language English Language students in Al-Makhwah. During the last period, many universities have adopted online learning due to the circumstances of the Corona pandemic. The researcher used analytical and descriptive methods, the questionnaire to clarify the relationship between online learning and its impact on students. The study used some questions asks 86 participants to elicit data. Through of the questionnaire it is clear that online learning has had advantages in terms of online learning because it provided easy access to information, saves effort and time, and the information. On the other hand, students faced some problems with the Internet and difficulties in communication with subject teachers. English language students will choose one appropriate option from the three options: Agree, agree somewhat and disagree. The main results of the study showed that: most of students said that Online learning increase your grades and online learning can keep efforts and time. Moreover, they disagreed with that the allowed time of the exams through online courses was not enough and online learning does not develop cooperative learning by a few of them. The study recommended that variation of online learning English language is enhancing understand English words. And teaching strategies of English language must take into consideration a wide scope knowledge of technical procedures through the lecture and to what extent the internet is available. In addition, students have to apply good time management to help them to use a lot of different kinds of online learning methods. Subject teachers of English Syllabus designers should increase and focus on terms of supporting English courses by another facilitators' techniques for using audiovisual aids for learning all branches of English language.